2022
DOI: 10.3389/fbioe.2022.927050
|View full text |Cite
|
Sign up to set email alerts
|

A Structured Scaffold Featuring Biomimetic Heterogeneous Architecture for the Regeneration of Critical-Size Bone Defects

Abstract: The regeneration of critical-size bone defects on long bones has remained a significant challenge because of the complex anatomical structure and vascular network. In such circumstances, current biomaterial forms with homogeneous structure and function can hardly satisfy the need for both osteogenesis and angiogenesis. In the current study, a heterogeneous biomimetic structured scaffold was constructed with the help of a 3D printed mold to simultaneously mimic the outer/inner periosteum and intermediate bone m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
1
1
Order By: Relevance
“…Our results showed that all the HGs showed a better drug-releasing ability of VEGF over the incubation time and higher VEGF drug release was observed with a higher concentration of VEGF-loaded HGs. The drug release profile further demonstrates that the HG could start releasing quantifiable VEGF after 6 h incubation and a significant release of VEGF by HGs was achieved on day 3 onwards, which is contradictory to the previous studies [52][53][54]. This could be due to the influence of the polymer's nature, such as the type, composition, and chemical bonding of the polymers, on the drug-releasing behavior of hydrogels.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Our results showed that all the HGs showed a better drug-releasing ability of VEGF over the incubation time and higher VEGF drug release was observed with a higher concentration of VEGF-loaded HGs. The drug release profile further demonstrates that the HG could start releasing quantifiable VEGF after 6 h incubation and a significant release of VEGF by HGs was achieved on day 3 onwards, which is contradictory to the previous studies [52][53][54]. This could be due to the influence of the polymer's nature, such as the type, composition, and chemical bonding of the polymers, on the drug-releasing behavior of hydrogels.…”
Section: Discussioncontrasting
confidence: 80%
“…Previous studies also proved the osteogenic stimulatory effect of HGs fabricated with nano-hydroxyapatite/collagen [6,65], chitosan/collagen [17,48], and hyaluronic acid/collagen [66]. Similarly, the osteogenic stimulatory effect of VEGF loaded in HGs was also demonstrated in several reports [37,54,67,68]. Several pieces of empirical evidence elucidated the actual signaling mechanism of VEGF in the osteogenesis of MSCs.…”
Section: Discussionmentioning
confidence: 77%